The Influence of Online Social Value Co-creation Activity on Consumer Purchase Intention: An Experimental Study - Shi, Ying; Zheng, Jinjin; Liang, Mo (Frontiers in Psychology, 2022)
Drawing from social interaction theory, this study explores the causal effect of social value co-creation on consumer purchase intention through three online experiments. The results show that social value co-creation can stimulate consumer purchase intention. Moreover, consumer-company identification plays a mediating role in linking social value co-creation to purchase intention. In addition, compared to low social norms, high social norms are more likely to weaken the influence of social value co-creation on consumers’ buying intention. The study provides both theoretical and practical implications to research area. Limitation and future research are also discussed.